RASIONALITAS MASYARAKAT MENYERAHKAN TANAH DALAM PEMBANGUNAN INFRASTRUKTUR JALAN DI DESA TUNGGUL KECAMATAN PACIRAN KABUPATEN LAMONGAN - Moh. Rizki Nur Salam (Balitbangda Provinsi Lampung, 2022)
The village government of Tunggul does physical development which absolutely requires land. The handover of land in the construction of road infrastructure in the village of Tunggul has been carried out since 2007 until now. However, the process of handing over land cannot be separated from problems. The handover of land involved most of the ownership rights to the land from the residents concerned, while the need for land was increasing. This study aims to identify the objective social and economic conditions of the people who gave up the land, identify the process of handing over the land, and to analyze the rationality of the people who gave up the land. This study uses a qualitative approach with Max Weber's rationality perspective. The results of this study indicate that the socio-economic objective conditions of landowners who hand over land vary starting from education, social status, occupation, income and expenses, needs, and wealth. The process of handing over the land goes through several stages, namely planning, preparation, implementation, and evaluation. The actions of landowners are divided into acts of instrumental rationality and value-oriented rationality actions. The act of instrumental rationality namely the land owner wants a new village road infrastructure and the land owner has the desire to sell his land (profit value). The action of rationality is value-oriented namely the land owner considers religious values ​​as a form of worship and the land owner does good deeds.